Impact of CYBA genotypes on severity and progression of multiple sclerosis. (6th February 2022) - Törnell, Andreas; Kiffin, Roberta; Haghighi, Sara; Mossberg, Natalia; Andersen, Oluf; Hellstrand, Kristoffer; Martner, Anna
Abstract: Background and purpose: The NOX2 enzyme of myeloid cells generates reactive oxygen species (ROS) that have been implicated in the pathology of multiple sclerosis (MS). We aimed to determine the impact of genetic variation within CYBA, which encodes the functional CYBA/p22 phox subunit of NOX2, on MS severity and progression. Methods: One hundred three MS patients with up to 49 (median = 17) years follow‐up time from first MS diagnosis were genotyped at the single nucleotide polymorphisms rs1049254 and rs4673 within CYBA . Results were matched with disease severity and time to diagnosis of secondary progressive MS (SPMS). NOX2‐mediated formation of ROS was measured by chemiluminescence in blood myeloid cells from healthy donors ( n = 55) with defined genotypes at rs1049254 and rs4673. Results: The rs1049254/G and rs4673/A CYBA alleles were associated with reduced formation of ROS and were thus defined as low‐ROS alleles. Patients carrying low‐ROS alleles showed reduced multiple sclerosis severity score ( p = 0.02, N = 103, linear regression) and delayed onset of SPMS ( p = 0.02, hazard ratio [HR] = 0.46, n = 100, log‐rank test). In a cohort examined after 2005, patients carrying low‐ROS CYBA alleles showed >20 years longer time to secondary progression ( p = 0.003, HR = 0.29, n = 59, log‐rank test). Conclusions: These results implicate NOX2 in MS, in particular for the development of secondary progressive disease, and point toward NOX2‐reductive therapy aiming to delay secondary progression. Abstract : Single nucleotide polymorphisms within the gene encoding the NOX2 subunit CYBA were found to impact on formation of NOX2‐derived reactive oxygen species (ROS). Multiple sclerosis (MS) patients carrying low‐ROS CYBA alleles showed reduced disease severity and delayed onset of secondary progressive MS.